KUALITAS VISUM ET REPERTUM PERLUKAAN DI RSUD KEPULAUAN MERANTI PERIODE 1 JANUARI 2010 - 31 DESEMBER 2013 - Achsanul Kubri; Dedi Afandi; Laode Burhauddin Mursali (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTVisum et Repertum (VeR) is a written report by a sworn doctor and has theauthority of what he/she has seen and and found in the evidence presented. The mostfrequent VeR requested by investigators is VeR of injury. A good quality of VeR isrequired in view of its important role in litigation of a criminal offense. This studywas aimed to understand the quality of VeR of injury in Kepulauan MerantiGeneral Hospital during 1 January 2010-31 December 2013. The research wasan observational study using descriptive retrospective design. This study usedHerkutanto’s scoring method towards 13 VeR substances. Samples of this studywere all data of VeR of injury that had fulfilled inclusion criteria. The total ofsamples were 70 samples of VeR. This study suggested that the highest number ofliving victims of injury cases was 27 victims (38,6%) in age group 22-40 years oldwith the most frequent sex was male as many as 43 victims (61,4%). The mostfrequent violence was blunt violence as many as 57 (81,4%) cases with the mostfrequent age group was 22-40 years old. The quality of VeR in preface was89,14% (good), in body part was 58,69% (medium) and in conclusion was39,28% (poor). In general, quality of VeR of injury in Kepulauan MerantiGeneral Hospital during 1 january 2010-31 december 2013 was 50% that couldbe categorized as medium quality.Keywords: Visum et Repertum, injury, quality of VeR of injury